Neuroprotective effect of methanolic extract of Sargassum wightii on rotenone-induced parkinsonism-like symptoms in Wistar albino rats - Sradhasini Rout; Bandana Rath; Subrat Kumar Bhattamisra; Anjan Kumar; Ishani Rath; Preetish Kumar Panigrahy (Shahrekord University of Medical Sciences, 2021)
Introduction: The pathogenesis of Parkinson's disease (PD) is multifactorial in which oxidative stress, neuroinflammation, and mitochondrial dysfunction are the leading factors. Currently, the antioxidant and anti-inflammatory agents of natural sources as neuroprotectants have raised much attention. The current study aimed to explore the neuroprotective effect of methanolic extract of Sargassum wightii in male Wistar albino rats against rotenone-induced PD. Methods: The rats were administered with rotenone (10 mg/kg orally) daily for 28 days to induce PD. S. wightii (200 mg/kg and 400 mg/kg) and levodopa+carbidopa combination (10 mg/kg) were administered to different groups of rats one hour prior to rotenone for 28 days. Behavioral parameters (akinesia, tremor, motor coordination, and locomotor activities) and body weight were recorded on days 14th and 28th of drug treatment. On the 28th day, the animals were sacrificed for the neurobiochemical analyses of brain tissue. Results: Rotenone treatment caused a significant reduction in behavioural parameters (P < 0.001), neurochemical deficits (P < 0.001), and elevation of oxidative stress markers (P < 0.001) in the brain. Pre-treatment with S. wightii at 200 mg/kg and 400 mg/kg doses significantly attenuated the rotenone-induced behavioral alterations and restored the mitochondrial NADH dehydrogenase activity and dopamine level in the striatum (P < 0.001). Moreover, 400 mg/kg of S. wightii restored the rotenone-induced increased oxidative stress markers like malondialdehyde (MDA), superoxide dismutase (SOD), and reduced glutathione (GSH) in the striatum (P < 0.01). Conclusion: S. wightii has provided a neuroprotective effect, probably by virtue of its antioxidant and dopamine restoring potential. Hence, it may offer a promising and new therapeutic lead for the treatment of PD but needs further research.